PENGARUH PROGRAM MARKETING PUBLIC RELATIONS TERHADAP KEPUTUSAN BERKUNJUNG DI PANTAI PANGANDARAN (Survei pada Wisatawan yang Berkunjung ke Destinasi Pariwisata Pantai Pangandaran) - Wijaya, Christy Regina; Waluya, Bagja; Setyorini, Heri Puspito Diyah (Universitas Pendidikan Indonesia, 2012)
Pangandaran beach is one tourism destination in West Java, situated in the district of Ciamis Â± 92 km south of the town of Ciamis. Pangandaran beach tourism destination, the type of nature tourism which is famous for its beaches. However, a decline in the level of tourist arrivals caused by several factors: less optimal promotion by tourism destination managers Pangandaran beach, unavailability of information centers which provide services to tourists, and tsunami disaster in July 2006 which destroyed most of the existing facilities in the area of Pangandaran beach. Because it would need to hold research to increase tourist visit through marketing public relations programs implemented by the managers of Pangandaran beach tourism destination. The research problem: 1)How does an idea a marketing public relations, 2)How is the idea of the decision to visit, 3)How does a marketing public relations visiting decision. This study aims to obtain an overview of marketing public relations, to obtain a marketing public relations descriptions, of the visiting decision and the influence of marketing public relations visiting decision. Data analysis technique are used path analysis (path analysis) with a sampling technique used systematic random sampling of 100 respondents. The results showed that the marketing public relations programs have a significant influence on the decision to visit. The biggest influence of marketing public relations programs visiting decision obtained through events and the smallest effect is obtained through public service activities. As for suggestions for tourism destination managers Pangandaran beach, should be more social activities to publications tourist or private sector to participate in this social activities, and make social activities are held regularly on the agenda the manager of Pangandaran beach tourism destination.